1-[(2-Chloro-7-methyl-3-quinolyl)methyl]pyridin-2(1H)-one - Roopan, S. Mohana (International Union of Crystallography, 2010)
In the title compound, C(16)H(13)ClN(2)O, the quinoline ring system is essentially planar, with a maximum deviation of 0.021 (2) Å. The pyridone ring is oriented at a dihedral angle of 85.93 (6)° with respect to the quinoline ring system. In the crystal structure, intermolecular C—H⋯O hydrogen bonds link the molecules along the b axis. Weak π–π stacking interactions [centroid–centroid distances = 3.7218 (9) and 3.6083 (9) Å] are also observed.